Rigidez do solo na estimativa da área de contato pneu-solo de um trator agrícola - THORPE, Davi de Farias (2022)
The estimation of the contact area assists in determining the contact pressure, the stress-strain relationship, and the potential risk of compaction; therefore, it is essential to know the shape and size of the tire-ground contact area. Some characteristics can change the tire-ground contact area, depending on the tire type, size, inflation pressure and axle load, as well as depending on soil characteristics such as texture, moisture, and resistance to deformation; however, not all these characteristics are considered in the models to obtain the contact area. The objective was to evaluate the influence of the stiffness of agricultural surfaces on the tire-soil contact area of an agricultural tractor. The study was carried out at the Carpina Sugarcane Experimental Station, Carpina-PE. Four areas were selected according to the levels of rigidity of their surfaces, namely: an agricultural soil after preparation, a soil cultivated with sugarcane after nine harvests, a compacted side road and a simple concrete surface. The contact area of three different tires was experimentally determined by means of photographic image analysis and theoretically by the super-ellipse model. The theoretical area obtained overestimated that obtained experimentally. The contact area showed an inversely proportional relationship to the density and directly proportional to the soil moisture content. The shape of the contact area did not suffer great variations in the tires of the front axle, however the rear tire presented great variation. The experimental shapes of the contact area approached the theoretical in the scenario with higher moisture content. It was concluded that surface stiffness reduced the size and changed the shape of the contact area; the super-ellipse model can overestimate the size of the actual contact area by up to 2 times. The moisture content was determinant on the shape and size of the contact area.